2019
DOI: 10.1002/jbm.a.36641
|View full text |Cite
|
Sign up to set email alerts
|

Efficient intrahepatic tumor generation by cell sheet transplantation to fabricate orthotopic hepatocarcinoma‐bearing model mice for drug testing

Abstract: Subcutaneous tumor‐bearing mice are commonly used to evaluate antitumor activity in preclinical studies of anticancer drugs. However, these models often exhibit excessive antitumor responses to anticancer drug candidates. In this study, intrahepatic tumor‐bearing mice as orthotopic tumor models were fabricated by transplanting hepatocarcinoma cell monolayers (sheets) to investigate differences in ectopic versus orthotopic antitumor response. Cell sheets, harvested from temperature‐responsive cell culture dishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Basically, the cell sheet method has obvious advantage over the cell suspension method; this was proved in other previous studies (Suzuki et al, 2014). Akimoto transplanted hepatocarcinoma cell sheet orthotopically and successfully to induce efficient intrahepatic tumor (Akimoto et al, 2019). He also compared the immunological reaction between immunodeficient mice and immunocompetent mice by comparing cell sheet transplantation and cell suspension injection with mouse lung squamous cancer cells (KLN-205) and found that the inoculated cells had a better survival rate and a lower immunological reaction in the cell sheet group (Akimoto et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, the cell sheet method has obvious advantage over the cell suspension method; this was proved in other previous studies (Suzuki et al, 2014). Akimoto transplanted hepatocarcinoma cell sheet orthotopically and successfully to induce efficient intrahepatic tumor (Akimoto et al, 2019). He also compared the immunological reaction between immunodeficient mice and immunocompetent mice by comparing cell sheet transplantation and cell suspension injection with mouse lung squamous cancer cells (KLN-205) and found that the inoculated cells had a better survival rate and a lower immunological reaction in the cell sheet group (Akimoto et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For the immunodeficient mice, despite the decreased inflammatory response, the scaffold might still affect cell growth and activities (Rodriguez et al, 2009;Bouvet-Gerbettaz et al, 2014). Recently, because of the development of tissue engineering and tumor organ technology, cell sheet technology has earned attention of researchers recently (Suzuki et al, 2014;Kobayashi et al, 2018;Akimoto et al, 2019;Lu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%